Method for preparing composition with coated porous material
Through slit die coating technology and non-contact method, the density of porous materials and the viscosity of the coating solution are balanced, and the surface film coating is formed, which solves the problem of fluid penetration, improves the stability of porous materials and the maintenance of pore structure. It is suitable for In skin care and medical applications.
Patent Information
- Application Number
- CN202380042890.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-01
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to effectively control fluid penetration into pores of porous materials, affecting their repair performance and porosity. Especially in skin care and medical applications, the fluid absorption time is too long and the coating is easily permeable, destroying the porous structure.
Using slit die head coating technology, a thin film coating is formed by balancing the density of porous materials and the viscosity of the coating solution, ensuring that the coating mainly remains on the surface and preventing the coating from entering through a non-contact method. In the pore, the stability of the coating and the maintenance of the porous structure are improved.
The stability of the surface coating of porous materials and the maintenance of pore structure are achieved, the fluid absorption time is shortened, the delivery control of repair agents is improved, and it is suitable for cosmetic skin treatment and medical purposes.
Smart Images

Figure CN119278057A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a composition comprising a coated porous material, and to the corresponding composition. The present invention also relates to the use of the product in cosmetic skin treatment and in the treatment of stagnant wounds, split skin grafts and ulcers. Background Art
[0002] In order to deposit the material onto the substrate, various coating techniques are used, including chemical or physical vapor deposition, electrochemical techniques, spraying, slot die coating, etc. In particular, the use of electrostatic powder coating techniques to coat conductive substrates (such as metals) is well known. By this method, the powder coating material is electrostatically charged and then sprayed or blown onto the surface of the conductive material to which it adheres. The material is impregnated with the powder by means of electrostatic attraction between the positively charged or ionized powder and the negatively charged surface of the conductive material, and vice versa. This method is particularly used for painting metal products.
[0003] Another well-established technology for applying solutions to substrates, which are usually planar, is slot die coating. Slot die coating allows for the reliable coating of micrometer-thick layers on flat substrate surfaces at relatively high speeds, as shown, for example, in US7097673B2. The coating material is usually dissolved or suspended in a solution or slurry and applied to the surface of the substrate by a precision coating head called a slot die. Slot die coating is thus a continuous coating technology that delivers a quantitatively precise and usually low-viscosity material to a surface at relatively high speeds.
[0004] Common uses of slot die coating technology are generally limited to smooth, non-porous materials such as photographic films and paper. An important technical issue associated with coating porous substrates is how to predict and control the penetration of fluids into the pores, which directly affects the appearance, properties and performance of the resulting material. Porous materials are extremely attractive as controlled drug carriers due to their large surface area, tunable pore size and mechanical stability. In particular, porous materials are widely used in medical devices as antimicrobial, antithrombotic and wound healing agents. However, uncontrolled penetration of liquid coatings containing healing agents into the pores may negatively affect the repair properties of such devices. Therefore, the stability of liquid coatings on the surface of porous materials is particularly important for devices used for local drug delivery.
[0005] For applications in skin care treatments, it is important to minimize the absorption of the fluid in terms of the time required to wet the porous substrate, which is measured by the sinking time. Therefore, the sinking time is an important factor in order to maintain the porosity of the porous substrate. In addition, keeping the pores free of coating is important for medical applications because the pores serve as a dermal template in which cells can grow.
[0006] The difference between slot die coating (non-contact coating, by which the coating follows the surface topologically) and contact coating methods (such as knife coating or roller coating, or any type of printing, etc.) is that slot die coating lays an evenly distributed film on top of the porous material, while contact coating presses the coating into the substrate. Thus, the coating blocks and destroys the pores in a way that allows the coating to pass from the other side. Summary of the invention
[0007] In one aspect, the present invention relates to a method for preparing a composition comprising a porous material, wherein the porous material is substantially flat and comprises a plurality of open and interconnected pores having a pore surface, the method comprising the steps of:
[0008] a) providing a porous material, wherein the porous material is substantially flat and comprises a plurality of open and interconnected pores having a pore surface, wherein the density of the porous material is between 0.01 g / cm 3 Up to 1 g / cm 3 and wherein the average diameter of the pores is in the range of 10 µm to 150 µm;
[0009] b) providing a coating solution, wherein the coating solution has a viscosity in a range of 1 Pa·s to 20 Pa·s;
[0010] c) providing an applicator device for applying the coating solution onto the surface of the porous material, wherein the applicator device comprises a slot die;
[0011] d) applying a quantitative amount of the coating solution onto the surface of the porous material by moving the porous material and the applicator device relative to each other at a speed of 0.1 m to 10 m per minute to coat the porous material and form a liquid layer;
[0012] e) drying the liquid layer.
[0013] The method based on slot die technology according to the present invention allows to cover the surface of the porous material with a thin film coating, which mainly remains on the surface of the porous material and does not penetrate into the interior of the pores. This effect is achieved by balancing the density of the porous material and the viscosity of the applied coating solution. It has been found that it is possible to apply a coating solution with a viscosity in the range of 1 Pa·s to 20 Pa·s to a porous material with a very low density (from 0.01 g / cm 3 The density of the porous material increases by 10% to 30% after coating, which helps to keep the coated material on the surface of the substrate. At the same time, the porous structure of the porous material is maintained, which is critical for controlling the delivery of the repair agent.
[0014] In addition, the method according to the present invention is non-contact, so that the applicator device does not contact the surface of the porous material, especially in step d), the applicator device does not contact the surface of the porous material. This is achieved by positioning the applicator device at a distance from the surface of the porous material. When a contact method is adopted, the pores tend to be partially blocked by the coating solution entering the interior of the pores. Using a non-contact method, the coating is mainly retained on the surface of the porous material and does not penetrate into the interior of the pores.
[0015] In another aspect, the present invention relates to corresponding compositions, in particular to compositions obtainable by the process according to the present invention.
[0016] In a further aspect, the present invention relates to the use of a composition comprising a porous material obtainable by the process according to the present invention in cosmetic skin treatments, such as treating or preventing wrinkles, skin irritations, and as a medicament, in particular for the treatment of stasis wounds, split skin grafts and ulcers. DETAILED DESCRIPTION
[0017] In one aspect, the present invention relates to a method for preparing a composition comprising a porous material, wherein the porous material is substantially flat and comprises a plurality of open and interconnected pores having a pore surface, the method comprising the steps of:
[0018] a) providing a porous material, wherein the porous material is substantially flat and comprises a plurality of open and interconnected pores having a pore surface, wherein the density of the porous material is between 0.01 g / cm 3 Up to 1 g / cm 3 In the range of 0.02 g / cm 3 Up to 0.05 g / cm 3 The most preferred range is 0.02 g / cm 3 Up to 0.04 g / cm 3 and wherein the average diameter of the pores is in the range of 10 µm to 150 µm;
[0019] b) providing a coating solution, wherein the viscosity of the coating solution is in the range of 1 Pa·s to 20 Pa·s, preferably 8 Pa·s to 15 Pa·s, more preferably 10 Pa·s to 14 Pa·s;
[0020] c) providing an applicator device for applying the coating solution onto the surface of the porous material, wherein the applicator device comprises a slot die;
[0021] d) applying a quantitative amount of the coating solution onto the surface of the porous material by moving the porous material and the applicator device relative to each other at a speed of 0.1 m to 10 m per minute to coat the porous material and form a liquid layer;
[0022] e) drying the liquid layer.
[0023] In one embodiment, in the method of preparing a composition comprising a porous material, after coating to form a porous substrate of the composition, the density of the porous material increases by 10% to 30%, preferably by 10% to 20%.
[0024] In one embodiment, the coating solution applied on the surface of the porous material in step d) has a weight of 0.5 g / m 2 Up to 200 g / m 2 In the range of 10 g / m 2 Up to 100 g / m 2 The most preferred range is 10 g / m 2 Up to 30 g / m 2 In one embodiment, the coating solution applied on the surface of the porous material in step d) has a weight of 0.5 g / m 2 Up to 200 g / m 2 In one embodiment, the coating solution applied on the surface of the porous material in step d) has a weight of 10 g / m 2 Up to 100 g / m 2 In one embodiment, the coating solution applied on the surface of the porous material in step d) has a weight of 10 g / m 2 Up to 30 g / m 2 within the range.
[0025] In one embodiment, the thickness of the porous material is in the range of 100 μm to 5000 μm, preferably in the range of 500 μm to 3000 μm, and more preferably in the range of 1000 μm to 2000 μm.
[0026] In one embodiment, the thickness of the coating after step e) is in the range of 1 μm to 300 μm, preferably in the range of 2 μm to 50 μm, more preferably in the range of 5 μm to 10 μm.
[0027] In one embodiment, the coating solution in the method for preparing the composition comprising porous material comprises a solvent component and a film-forming component. In one embodiment, the solvent component is selected from water and alcohol such as ethanol, and mixtures thereof. In one embodiment, the solvent component is water. In a specific embodiment, the content of water in the coating solution is in the range of 0.5 wt % to 50 wt %, preferably in the range of 2 wt % to 35 wt %, more preferably in the range of 3 wt % to 30 wt %. In one embodiment, the film-forming component is selected from hyaluronic acid (HA), polyacrylate, polyurethane, and polysaccharides such as alginate, nanocellulose or carboxymethyl cellulose (CMC), or mixtures thereof. In one embodiment, the film-forming component is selected from hyaluronic acid (HA), carboxymethyl cellulose (CMC), polyacrylate and polyurethane, or mixtures thereof. In one embodiment, the film-forming component is a mixture of hyaluronic acid (HA) and carboxymethyl cellulose (CMC) and the solvent component is water. In one embodiment, the weight ratio of hyaluronic acid (HA) and carboxymethyl cellulose (CMC) in water ranges from 1:3 to 3:1, preferably from 1:2 to 2:1, and most preferably the weight ratio of hyaluronic acid (HA) and carboxymethyl cellulose (CMC) in water is 1:1. In one embodiment, the coating solution comprises 0.5% to 3% by weight of hyaluronic acid (HA), 0.5% to 3% by weight of carboxymethyl cellulose (CMC), and 94% to 99% by weight of water. In one embodiment, the coating solution comprises about 1% by weight of hyaluronic acid (HA), about 1% by weight of carboxymethyl cellulose (CMC), and about 98% by weight of water.
[0028] In one embodiment, the coating solution in the method for preparing a composition comprising a porous material comprises an emulgator. In one embodiment, the emulsifier is selected from polyglyceryl-10 laurate, glycerol, sucrose stearate, methyl glucose sesquistearate, glyceryl stearate, cetearyl glucoside, hydrogenated palm glycerides, polyethylene glycol, and mixtures thereof.
[0029] In one embodiment, the coating solution in the method for preparing a composition comprising a porous material comprises other ingredients selected from vitamin A, vitamin B, vitamin C, vitamin D, vitamin K, vitamin E and 4-[(1E, 3S)-3-vinyl-3,7-dimethylocta-1,6-dienyl]phenol (bakuchiol), or a mixture thereof. Preferably, the other ingredient is vitamin D.
[0030] In one embodiment, the porous material in the method of preparing the composition is in the form of a sheet, a dressing or a roll-up sheet. For a continuous mode of operation for coating the porous material with a coating solution, a roll-up sheet is an advantageous form.
[0031] The porous material in the method for preparing the composition is substantially flat, i.e. the thickness of the porous material over the entire length and width of the material deviates from the average thickness of the porous material by no more than ±20%, preferably by no more than ±10%. Thus, the porous substrate in the composition has two main surfaces, an upper side and a lower side (see Fig.23 ), which are in opposite directions and extend over the entire length and width of the substrate. For example, when the average thickness is 1 mm, the thickness of the material over its entire length and width is maintained in the range of 0.8 mm to 1.2 mm, preferably in the range of 0.9 mm to 1.1 mm. When the average thickness is 2 mm, the thickness of the substantially flat material over its entire length and width is maintained in the range of 1.6 mm to 2.4 mm, preferably in the range of 1.8 mm to 2.2 mm. In one embodiment, the porous material and the porous substrate are flat.
[0032] In one embodiment, the porous material in the method for preparing a composition comprising a porous material comprises at least 90% by weight of biological material, preferably the porous material comprises at least 95% by weight of biological material, more preferably the porous material comprises at least 98% by weight of biological material, and most preferably the porous material comprises at least 99% by weight of biological material.
[0033] In one embodiment, the density of the porous material in the method of preparing a composition comprising a porous material is between 0.01 g / cm 3 Up to 1 g / cm 3 In the range of 0.02 g / cm 3 Up to 0.05 g / cm 3 In the range of 0.02 g / cm 3 Up to 0.04 g / cm 3 The most preferred range is 0.022 g / cm 3 Up to 0.03 g / cm 3 .
[0034] In one embodiment, the average diameter of the pores in the porous material in the method for preparing a composition comprising a porous material is in the range of 10 µm to 150 µm. In one embodiment, the average diameter of the pores in the porous material in the method for preparing a composition comprising a porous material is in the range of 15 µm to 65 µm. In one embodiment, the average diameter of the pores in the porous material in the method for preparing a composition comprising a porous material is in the range of 15 µm to 40 µm. In one embodiment, the average diameter of the pores in the porous material in the method for preparing a composition comprising a porous material is in the range of 25 µm to 100 µm.
[0035] In one embodiment, the viscosity of the coating solution in the method for preparing a composition comprising a porous material is in the range of 1 Pa·s to 20 Pa·s. In a preferred embodiment, the viscosity of the coating solution in the method for preparing a composition comprising a porous material is in the range of 5 Pa·s to 20 Pa·s. In a more preferred embodiment, the viscosity of the coating solution in the method for preparing a composition comprising a porous material is in the range of 8 Pa·s to 15 Pa·s. In a still more preferred embodiment, the viscosity of the coating solution in the method for preparing a composition comprising a porous material is in the range of 10 Pa·s to 14 Pa·s.
[0036] In one embodiment, the density of the porous material in the method of preparing a composition comprising a porous material is between 0.01 g / cm 3 Up to 1 g / cm 3 and the viscosity of the coating solution is in the range of 1 Pa·s to 20 Pa·s. In a preferred embodiment, the density of the porous material in the method for preparing the composition is 0.02 g / cm 3 Up to 0.05 g / cm 3 In a more preferred embodiment, the density of the porous material in the method for preparing the composition is 0.02 g / cm 3 Up to 0.04 g / cm 3 and the viscosity of the coating solution is in the range of 10 Pa·s to 14 Pa·s.
[0037] In one embodiment, the porous material in the method of preparing a composition comprising a porous material is a biological material.
[0038] In one embodiment, the porous material in the method for preparing a composition comprising a porous material is selected from natural and / or synthetic polymers, or mixtures thereof, in particular polysaccharides, glycosaminoglycans, proteins, or mixtures thereof.
[0039] In one embodiment, the porous material in the method of preparing a composition comprising a porous material is selected from collagen, alginates such as calcium alginate, hyaluronic acid, cellulose and vegetable proteins such as pea and soy, or a mixture thereof.
[0040] In one embodiment, the porous material in the method of preparing a composition comprising a porous material is collagen. In one embodiment, the porous material in the method of preparing a composition comprising a porous material is alginate, in particular calcium alginate.
[0041] In one embodiment, the porous material in the method for preparing the composition comprising the porous material is a mixture of collagen and calcium alginate. In one embodiment, the porous material comprises collagen in the range of 80% to 98% by weight and calcium alginate in the range of 2% to 20% by weight. In a preferred embodiment, the porous material comprises collagen in the range of 85% to 95% by weight and calcium alginate in the range of 5% to 15% by weight. In particular, the porous material comprises about 90% by weight of collagen and about 10% by weight of calcium alginate.
[0042] In one embodiment, the collagen in the porous material in the method of preparing a composition comprising a porous material is natural collagen of animal origin having a triple helical structure.
[0043] In one embodiment, the collagen in the porous material in the method of preparing a composition comprising a porous material is selected from type 1 collagen, type 3 collagen, type 5 collagen, or a mixture thereof.
[0044] In one embodiment of the method for preparing a composition comprising a porous material, applying a coating solution on the surface of the porous material is performed in the following manner: the porous material is positioned below a fixed slot die and moved horizontally below the slot die. In one embodiment, the moving speed of the porous material is in the range of 0.1 m to 10 m per minute.
[0045] In one embodiment of the method for preparing a composition comprising a porous material, the distance between the slot die and the surface of the porous material is at least 50 μm, preferably at least 100 μm, more preferably at least 200 μm.
[0046] In one embodiment of the method for preparing a composition comprising a porous material, the distance between the slot die and the surface of the porous material is in the range of 50 µm to 1000 µm, preferably 100 µm to 800 µm, more preferably 200 µm to 600 µm.
[0047] In one embodiment of the method for preparing a composition comprising a porous material, the solvent component of the coating solution is water, and the drying in step e) is carried out in such a way that the final content of water in the composition after drying is in the range of 5 wt % to 25 wt %, preferably in the range of 10 wt % to 18 wt %.
[0048] In one embodiment of the method for preparing a composition comprising a porous material, the drying in step e) is performed by supplying hot air to the liquid layer, wherein the temperature of the hot air is in the range of 30°C to 100°C, preferably in the range of 35°C to 50°C.
[0049] In another aspect, the present invention relates to a composition comprising a porous material obtainable by a method according to any of the preceding embodiments.
[0050] In a third aspect, the present invention relates to a composition comprising a porous material obtainable by a method according to any of the preceding embodiments for use as a medicament. In one embodiment, the present invention relates to a composition comprising a porous material obtainable by a method according to any of the preceding embodiments for use in the treatment of stasis wounds, split skin grafts and ulcers.
[0051] In a fourth aspect, the present invention relates to a composition comprising a porous material obtainable by a method according to any of the preceding embodiments, for use in cosmetic skin treatment. In one embodiment, the present invention relates to a composition comprising a porous material obtainable by a method according to any of the preceding embodiments, for use in treating or preventing wrinkles and skin irritation.
[0052] In a fifth aspect, the present invention relates to the use of a composition comprising a porous material obtainable by a method according to any of the preceding embodiments for the treatment of stasis wounds, split skin grafts and ulcers.
[0053] In a sixth aspect, the present invention relates to the use of a composition comprising a porous material obtainable by a method according to any of the preceding embodiments in cosmetic skin treatment, such as treating or preventing wrinkles and skin irritations.
[0054] In a seventh aspect, the present invention relates to a method of treating stasis wounds, split skin grafts and ulcers, the method comprising administering to a subject in need thereof a composition comprising a porous material obtainable by a method according to any of the preceding embodiments.
[0055] In an eighth aspect, the present invention relates to a composition comprising,
[0056] - a porous substrate comprising a first major surface and a second major surface, wherein the porous substrate is substantially planar and comprises a plurality of open and interconnected pores having a pore surface, the pores extending through the substrate from the first major surface to the second major surface, wherein the average diameter of the pores is in the range of 10 μm to 150 μm;
[0057] - a coating on the first major surface and / or on the second major surface, wherein the coating comprises hyaluronic acid (HA), polyacrylate, polyurethane, or a polysaccharide such as alginate, nanocellulose or carboxymethylcellulose (CMC), or a mixture thereof.
[0058] It is characterized in that the water absorption of the composition is in the range of 10 g to 50 g per gram of the composition, preferably 20 g to 40 g per gram of the composition.
[0059] In one embodiment, the thickness of the porous substrate is in the range of 1 mm to 5 mm, preferably 1 mm to 3 mm, more preferably 1 mm to 2 mm, and the water absorption of the composition is in the range of 20 g to 40 g per gram of the composition.
[0060] In one embodiment, the water absorption of the composition deviates from the water absorption of the uncoated porous substrate, preferably collagen, by no more than ±50%, preferably by no more than ±40%, more preferably by no more than ±30%, and most preferably by no more than ±20%.
[0061] In a preferred embodiment, the water absorption of the composition is in the range of 25 g to 35 g per gram of the composition.
[0062] In one embodiment, the thickness of the porous substrate is in the range of 1 mm to 2 mm, and the water absorption of the composition is in the range of 25 g to 35 g per gram of the composition.
[0063] In one embodiment, the coating in the composition is bonded to the first major surface and / or the second major surface of the porous substrate via non-covalent bonds.
[0064] In one embodiment, the composition does not include a crosslinking agent that binds the porous substrate and the coating together.
[0065] In some embodiments, the coating on the first major surface and / or the second major surface of the porous substrate further comprises water and / or an alcohol such as ethanol. In some embodiments, the coating on the first major surface and / or the second major surface comprises water.
[0066] In a preferred embodiment, the coating comprises hyaluronic acid (HA), carboxymethylcellulose (CMC) and water.
[0067] In some embodiments, the amount of the coating in the composition is in the range of 0.1 wt % to 10 wt %, preferably 0.5 wt % to 3 wt %, relative to the weight of the substrate.
[0068] In some embodiments, at least 80%, preferably at least 90%, more preferably at least 95%, and most preferably at least 99% of the first major surface and / or the second major surface is covered by the coating.
[0069] In some embodiments, the second major surface of the porous substrate does not include the coating. In one embodiment, the coating on the first major surface and / or the second major surface of the porous substrate further includes an emulsifier. In one embodiment, the emulsifier is selected from polyglyceryl-10 laurate, glycerin, sucrose stearate, methyl glucose sesquistearate, glyceryl stearate, cetearyl glucoside, hydrogenated palm glycerides, polyethylene glycol, and mixtures thereof.
[0070] In one embodiment, the coating on the first major surface and / or the second major surface of the porous substrate further comprises an ingredient selected from the following substances: vitamin A, vitamin B, vitamin C, vitamin D, vitamin K, vitamin E and 4-[(1E, 3S)-3-vinyl-3,7-dimethylocta-1,6-dienyl]phenol (bakuchiol), or a mixture thereof. Preferably, the other ingredient is vitamin D.
[0071] In one embodiment, the porous substrate in the composition comprises at least 90% by weight of the biological material, preferably the porous substrate comprises at least 95% by weight of the biological material, more preferably the porous substrate comprises at least 98% by weight of the biological material, and most preferably the porous substrate comprises at least 99% by weight of the biological material.
[0072] In one embodiment, the average diameter of the pores in the porous substrate of the composition is in the range of 10 μm to 150 μm. In one embodiment, the average diameter of the pores in the porous substrate of the composition is in the range of 15 μm to 65 μm. In one embodiment, the average diameter of the pores in the porous substrate of the composition is in the range of 15 μm to 40 μm. In one embodiment, the average diameter of the pores in the porous substrate of the composition is in the range of 25 μm to 100 μm.
[0073] In one embodiment, the porous substrate in the composition is a biological material.
[0074] In one embodiment, the porous substrate in the composition is selected from natural and / or synthetic polymers, or mixtures thereof, in particular polysaccharides, glycosaminoglycans, proteins, or mixtures thereof.
[0075] In one embodiment, the porous matrix in the composition is selected from collagen, alginate such as calcium alginate, hyaluronic acid, cellulose, and vegetable protein such as pea and soy, or a mixture thereof.
[0076] In one embodiment, the porous substrate in the composition is collagen. In one embodiment, the porous substrate in the composition is alginate, in particular calcium alginate.
[0077] In one embodiment, the porous substrate in the composition is a mixture of collagen and calcium alginate. In one embodiment, the porous substrate comprises collagen in the range of 80% to 98% by weight and calcium alginate in the range of 2% to 20% by weight. In a preferred embodiment, the porous substrate comprises collagen in the range of 85% to 95% by weight and calcium alginate in the range of 5% to 15% by weight. In particular, the porous substrate comprises about 90% by weight of collagen and about 10% by weight of calcium alginate.
[0078] In one embodiment, the collagen in the porous matrix is natural collagen of animal origin having a triple helical structure.
[0079] In one embodiment, the collagen in the porous substrate is selected from type 1 collagen, type 3 collagen, type 5 collagen, or a mixture thereof.
[0080] In some embodiments, the composition as defined in any of the preceding embodiments is prepared using a method according to any of the above embodiments.
[0081] In a ninth aspect, the invention relates to a composition according to any of the preceding embodiments for use in cosmetic skin treatment. In one embodiment, the invention relates to a composition according to any of the preceding embodiments for use in treating or preventing wrinkles and skin irritation.
[0082] In a tenth aspect, the invention relates to the use of the composition according to any of the preceding embodiments for the treatment of stasis wounds, split skin grafts and ulcers.
[0083] In an eleventh aspect, the invention relates to the use of a composition according to any of the preceding embodiments for cosmetic skin treatment, such as for the treatment or prevention of wrinkles and skin irritations.
[0084] In a twelfth aspect, the invention relates to a method of treating stasis wounds, split skin grafts and ulcers, the method comprising administering to a subject in need thereof a composition according to any of the preceding embodiments.
[0085] In the above case, the following consecutively numbered embodiments provide further specific aspects of the present invention:
[0086] 1. A method for preparing a composition comprising a porous material, wherein the porous material is substantially flat and comprises a plurality of open and interconnected pores having a pore surface, the method comprising the following steps:
[0087] a) providing a porous material, wherein the porous material is substantially flat and comprises a plurality of open and interconnected pores having a pore surface, wherein the density of the porous material is between 0.01 g / cm 3 Up to 1 g / cm 3 In the range of 0.02 g / cm 3 Up to 0.05 g / cm 3 The most preferred range is 0.02 g / cm 3 Up to 0.04 g / cm 3 and wherein the average diameter of the pores is in the range of 10 µm to 150 µm;
[0088] b) providing a coating solution, wherein the viscosity of the coating solution is in the range of 1 Pa·s to 20 Pa·s, preferably 5 Pa·s to 20 Pa·s, more preferably 8 Pa·s to 15 Pa·s, even more preferably 10 Pa·s to 14 Pa·s;
[0089] c) providing an applicator device for applying the coating solution onto the surface of the porous material, wherein the applicator device comprises a slot die;
[0090] d) applying a quantitative amount of the coating solution onto the surface of the porous material by moving the porous material and the applicator device relative to each other at a speed of 0.1 m to 10 m per minute to coat the porous material and form a liquid layer;
[0091] e) drying the liquid layer.
[0092] 2. The method for preparing a composition comprising a porous material according to embodiment 1, wherein the density of the porous material increases by 10% to 30%, preferably by 10% to 20%, after coating.
[0093] 3. The method for preparing a composition comprising a porous material according to embodiment 1 or 2, wherein the coating solution applied on the surface of the porous material in step d) has a quantitative concentration of 0.5 g / m 2 Up to 200 g / m 2 In the range of 10 g / m 2 Up to 100 g / m 2 The most preferred range is 10 g / m 2 Up to 30 g / m 2 within the range.
[0094] 4. The method for preparing a composition comprising a porous material according to any one of embodiments 1 to 3, wherein the coating solution comprises a solvent component and a film-forming component.
[0095] 5. The method for preparing a composition comprising a porous material according to embodiment 4, wherein the solvent component is water.
[0096] 6. The method for preparing a composition comprising a porous material according to embodiment 5, wherein the water content in the coating solution is in the range of 0.5 wt % to 50 wt %, preferably in the range of 2 wt % to 35 wt %, and more preferably in the range of 3 wt % to 30 wt %.
[0097] 7. A method for preparing a composition comprising a porous material according to any of embodiments 4 to 6, wherein the film-forming component is selected from hyaluronic acid (HA), polyacrylates, polyurethanes, and polysaccharides such as alginate, nanocellulose or carboxymethyl cellulose (CMC), or a mixture thereof.
[0098] 8. The method for preparing a composition comprising a porous material according to any one of embodiments 1 to 7, wherein the coating solution comprises an emulsifier.
[0099] 9. A method for preparing a composition comprising a porous material according to embodiment 8, wherein the emulsifier is selected from polyglyceryl-10 laurate, glycerin, sucrose stearate, methyl glucose sesquistearate, glyceryl stearate, cetearyl glucoside, hydrogenated palm glyceride, polyethylene glycol, or a mixture thereof.
[0100] 10. A method for preparing a composition comprising a porous material according to any of embodiments 1 to 9, wherein the coating solution comprises other ingredients selected from vitamin A, vitamin B, vitamin C, vitamin K, vitamin E and 4-[(1E,3S)-3-vinyl-3,7-dimethylocta-1,6-dienyl]phenol (bakuchiol), or a mixture thereof.
[0101] 11. The method for preparing a composition comprising a porous material according to any one of embodiments 1 to 10, wherein the porous material is a biological material.
[0102] 12. A method for preparing a composition comprising a porous material according to embodiment 11, wherein the biomaterial is selected from natural and / or synthetic polymers, or mixtures thereof, in particular polysaccharides, glycosaminoglycans, proteins and / or synthetic polymers, or mixtures thereof.
[0103] 13. The method for preparing a composition comprising a porous material according to embodiment 11 or 12, wherein the biomaterial is selected from collagen, alginate, hyaluronic acid, cellulose and plant proteins such as pea and soybean.
[0104] 14. The method for preparing a composition comprising a porous material according to embodiment 13, wherein the biomaterial is collagen.
[0105] 15. The method for preparing a composition comprising a porous material according to embodiment 14, wherein the biomaterial is natural collagen of animal origin having a triple helical structure.
[0106] 16. The method for preparing a composition comprising a porous material according to any one of embodiments 1 to 15, wherein applying a coating solution onto the surface of the porous material is performed in the following manner: the porous material is positioned below a fixed slot die and horizontally moved below the slot die.
[0107] 17. The method for preparing a composition comprising a porous material according to any of embodiments 1 to 16, wherein the distance between the slot die and the surface of the porous material is in the range of 50 µm to 1000 µm, preferably 100 µm to 800 µm, more preferably 200 µm to 600 µm.
[0108] 18. The method for preparing a composition comprising a porous material according to any of embodiments 1 to 17, wherein the drying in step e) is performed by supplying hot air to the liquid layer, wherein the temperature of the hot air is in the range of 30°C to 100°C, preferably in the range of 35°C to 50°C.
[0109] 19. The method for preparing a composition comprising a porous material according to any one of embodiments 1 to 18, wherein the porous material is in the form of a sheet, a dressing or a rolled sheet.
[0110] 20. A composition comprising:
[0111] - a porous substrate comprising a first major surface and a second major surface, wherein the porous substrate is substantially planar and comprises a plurality of open and interconnected pores having a pore surface, the pores extending through the porous substrate from the first major surface to the second major surface, wherein the average diameter of the pores is in the range of 10 μm to 150 μm;
[0112] - a coating on the first major surface and / or on the second major surface of the porous substrate, wherein the coating comprises hyaluronic acid (HA), polyacrylate, polyurethane, or a polysaccharide such as alginate, nanocellulose or carboxymethylcellulose (CMC), or a mixture thereof;
[0113] It is characterized in that the water absorption of the composition is in the range of 10 g to 50 g per gram of the composition, preferably 20 g to 40 g per gram of the composition.
[0114] 21. The composition according to embodiment 20, wherein the coating in the composition is bonded to the first major surface and / or the second major surface of the porous substrate by non-covalent bonds.
[0115] 22. The composition of embodiment 20 or 21, wherein the composition does not comprise a crosslinker that binds the porous substrate and the coating together.
[0116] 23. The composition of any of embodiments 20 to 22, wherein the coating on the first major surface and / or on the second major surface further comprises water.
[0117] 24. The composition according to any of embodiments 20 to 23, wherein the amount of coating in the composition is in the range of 0.1 wt % to 10 wt %, preferably 0.5 wt % to 3 wt %, relative to the weight of the composition.
[0118] 25. The composition according to any of embodiments 20 to 24, wherein at least 80%, preferably at least 90%, more preferably at least 95%, most preferably at least 99% of the first major surface and / or the second major surface is covered by the coating.
[0119] 26. The composition of any of embodiments 20 to 25, wherein the coating on the first major surface and / or the second major surface of the porous substrate further comprises an emulsifier.
[0120] 27. A composition according to any of embodiments 20 to 26, wherein the coating on the first major surface and / or the second major surface of the porous substrate further comprises an ingredient selected from the following substances: vitamin A, vitamin B, vitamin C, vitamin D, vitamin K, vitamin E and 4-[(1E,3S)-3-vinyl-3,7-dimethylocta-1,6-dienyl]phenol (bakuchiol), or a mixture thereof.
[0121] 28. A composition according to any of embodiments 20 to 27, wherein the porous substrate in the composition comprises at least 90% by weight of biomaterial, preferably at least 95% by weight of biomaterial, more preferably at least 98% by weight of biomaterial, and most preferably at least 99% by weight of biomaterial.
[0122] 29. A composition according to any of embodiments 20 to 28, wherein the porous substrate in the composition is a biomaterial.
[0123] 30. The composition according to any of embodiments 20 to 29, wherein the porous substrate in the composition is selected from natural and / or synthetic polymers, or mixtures thereof, in particular polysaccharides, glycosaminoglycans, proteins, or mixtures thereof.
[0124] 31. The composition according to any of embodiments 20 to 30, wherein the porous matrix in the composition is selected from collagen, alginates such as calcium alginate, hyaluronic acid, cellulose, and vegetable proteins such as pea and soy, or mixtures thereof.
[0125] 32. A composition according to embodiment 31, wherein the porous substrate in the composition is collagen.
[0126] 33. A composition according to embodiment 31 or 32, wherein the porous matrix in the composition is a mixture of collagen and calcium alginate.
[0127] 34. The composition according to any of embodiments 31 to 33, wherein the collagen in the porous matrix is natural collagen of animal origin having a triple helical structure.
[0128] 35. The composition according to any of embodiments 31 to 34, wherein the collagen in the porous matrix is selected from type 1 collagen, type 3 collagen, type 5 collagen, or a mixture thereof.
[0129] 36. A composition obtainable by the method according to any of embodiments 1 to 19.
[0130] 37. A composition according to any of embodiments 20 to 36 for use as a medicament.
[0131] 38. The composition according to any of embodiments 20 to 36, for use in the treatment of stasis wounds, split skin grafts and ulcers.
[0132] 39. A composition according to any of embodiments 20 to 36 for use in cosmetic skin treatment such as treating or preventing wrinkles and skin irritation.
[0133] 40. Use of the composition according to any of embodiments 20 to 36 for treating stasis wounds, split skin grafts and ulcers.
[0134] 41. Use of a composition according to any of embodiments 20 to 36 in cosmetic skin treatment, such as treating or preventing wrinkles and skin irritation.
[0135] 42. A method of treating stasis wounds, split skin grafts and ulcers, the method comprising administering to a subject in need thereof a composition according to any of embodiments 20 to 36.
[0136] definition
[0137] Listed below are definitions of various terms used to describe the present invention. Unless limited individually or as part of a larger group in specific cases, these definitions apply to the terms used in this specification and claims. Unless otherwise defined, all technical and scientific terms used herein generally have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs.
[0138] As used herein, the articles "a" and "an" refer to one or more than one (ie, at least one) of the grammatical object of the article. For example, "an element" refers to at least one element, ie, one element or more than one element.
[0139] As used herein, the term "porous material" refers to a material containing pores (ie, cavities, channels, or interstices) wherein the depth of the pores exceeds their average diameter.
[0140] As used herein, the term "porous substrate" refers to the porous material of the composition onto which the coating is applied.
[0141] Unless specifically defined otherwise, the term "thickness" in relation to a porous material refers to the average thickness of the porous material.
[0142] As used herein, the term "substantially planar" means that the thickness of the material throughout its length and width does not vary from an average thickness by more than ±20%, preferably by more than ±10%.
[0143] As used herein, the term "sheet" refers to a substantially flat material, wherein the thickness of the material is in the range of 1 mm to 8 mm.
[0144] As used herein, the terms "rolled material" and "rolled sheet" are used interchangeably and refer to a sheet of porous material wound in a cylindrical form around the central axis of the roll from which material may be removed from the center or inner periphery of the roll.
[0145] As used herein, the term "dressing" refers to a composition comprising a film-coated porous material further coated with a layer of an additional polymer, wherein the composition is in the form of a sheet.
[0146] As used herein, the term "applicator device" refers to a device suitable for applying a liquid onto the surface of a material.
[0147] As used herein, the term "solvent component" refers to a liquid comprising a single solvent or a mixture of solvents that is suitable for dissolving or dispersing one or more of the various substances. Non-limiting examples of such solvents include water and alcohols such as ethanol or isopropanol.
[0148] As used herein, the term "film-forming component" refers to a substance that can form a film when applied to a solid surface. In particular, the film-forming component is applied to the surface in the form of a liquid layer, and the film is formed after the liquid layer is dried in air. Non-limiting examples of film-forming components include hyaluronic acid (HA), carboxymethyl cellulose (CMC), nanocellulose, alginate, polyacrylate and polyurethane.
[0149] As used herein, the term "emulsifier" refers to a substance that promotes the mixing of immiscible liquids of different polarities, such as water, with lipophilic ingredients. Non-limiting examples of emulsifiers include polyglyceryl-10 laurate, polyglyceryl-10 laurate, glycerol, sucrose stearate, methyl glucose sesquistearate, glyceryl stearate, cetearyl glucoside, hydrogenated palm glycerides, polyethylene glycol.
[0150] As used herein, the term "coating" refers to a thin deposit of material that substantially covers the surface of a substrate.
[0151] As used herein, the term "salt" refers to an ionic compound composed of an ionic combination of positively charged cations and negatively charged anions.
[0152] As used herein, the term "biomaterial" refers to a natural or synthetic biocompatible material suitable for use in a medical device intended to interact with a biological system. Non-limiting examples include collagen, gelatin, alginate, and polysaccharides such as glycosaminoglycans.
[0153] As used herein, the term "polysaccharide" refers to a polymer comprising a backbone comprising predominantly (at least 90%) monosaccharide repeating units and / or derivatized monosaccharide repeating units.
[0154] As used herein, the term "protein" or "polypeptide" refers to a polymer of two or more natural amino acids or unnatural amino acids.
[0155] As used herein, the term "glycosaminoglycan" refers to a group of acidic polysaccharides, each having a repeating unit of a disaccharide composed of an amino sugar and uronic acid or galactose.
[0156] As used herein, the term "alginate" refers to an anion of alginic acid. Therefore, the terms "alginate" and "alginate salt" are used interchangeably in the context of the present invention. Alginate can be, for example, calcium alginate. Alginate is a linear polymer formed by combining anions of β-D-mannuronic acid (M, β-D-mannuronic acid) and anions of α-L-guluronic acid (G, α-L-guluronic acid) by means of 1-4 glycosidic bonds.
[0157] As used herein, the term "collagen" refers to an extracellular family of fibrous proteins characterized by their rigid triple helical structure. Three collagen polypeptide chains ("α chains") are wound around each other to form the helical molecule.
[0158] As used herein, the term "subject" refers to a human or non-human mammal. Preferably, the subject is a human. BRIEF DESCRIPTION OF THE DRAWINGS
[0159] Figure 1 Schematic diagram showing the slot die coating process.
[0160] Figure 2 Shown is a SEM (scanning electron microscope) image of a collagen matrix without coating, top view.
[0161] Figure 3 Shown is a SEM (scanning electron microscope) image of a collagen matrix with CMC coating, top view.
[0162] Figure 4 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 1) with a 1% HA coating (20 µm) applied by a non-contact slot die method, top view.
[0163] Figure 5 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 1) with a 1% HA coating (20 µm) applied by a non-contact slot die method, cross section (150x magnification).
[0164] Figure 6 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 1) with a 1% HA coating (20 µm) applied by a non-contact slot die method, cross section (1500x magnification).
[0165] Figure 7Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 1) with a 1% HA coating (20 µm) applied by a non-contact slot die method, bottom view.
[0166] Figure 8 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 2) with a 1% HA coating (40 µm) applied by a non-contact slot die method, top view.
[0167] Fig. 9 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 2) with a 1% HA coating (40 µm) applied by a non-contact slot die method, cross section (150x magnification).
[0168] Fig.10 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 2) with a 1% HA coating (40 µm) applied by a non-contact slot die method, cross section (1500x magnification).
[0169] Fig.11 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 2) with a 1% HA coating (40 µm) applied by a non-contact slot die method, bottom view.
[0170] Fig.12 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 3) with a 1% HA coating (30 µm) applied by a contact slot die method, top view.
[0171] Fig.13 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 3) with a 1% HA coating (30 µm) applied by a contact slot die method, cross section (150x magnification).
[0172] Fig.14 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 3) with a 1% HA coating (30 µm) applied by a contact slot die method, cross section (1500x magnification).
[0173] Fig.15 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 2, Experiment 3) with a 1% HA coating (30 µm) applied by a contact slot die method, bottom view.
[0174] Fig.16 Shown is a SEM (scanning electron microscope) image of a collagen matrix without coating, cross section (150× magnification).
[0175] Fig.17 Shown is a SEM (scanning electron microscope) image of a collagen matrix without coating, cross section (1500x magnification).
[0176] Fig.18 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 3) with a 0.4% HA coating (40 µm) applied by a non-contact slot die method, top view.
[0177] Fig.19 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 3) with a 0.4% HA coating (40 µm) applied by a non-contact slot die method, cross section (100x magnification).
[0178] Fig. 20 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 3) with a 0.4% HA coating (40 µm) applied by a non-contact slot die method, in cross section from the upper side (1500x magnification).
[0179] Fig.21 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 3) with a 0.4% HA coating (40 µm) applied by a non-contact slot die method, cross-sectioned to the lower side (1500x magnification).
[0180] Fig. 22 Shown is a SEM (scanning electron microscope) image of a collagen matrix (Example 3) with a 0.4% HA coating (40 µm) applied by a non-contact slot die method, bottom view.
[0181] Fig.23 The orientation of the two major surfaces of the uncoated collagen matrix is shown.
[0182] Example
[0183] Example 1.
[0184] Coating solution 1
[0185] • CMC (carboxymethyl cellulose): 3.3% by weight
[0186] • Water: 96.7% by weight.
[0187] Coating solution 2
[0188] • Vitamin C: 25% by weight
[0189] • CMC (carboxymethyl cellulose): 3.3% by weight
[0190] • Water: 71.7% by weight.
[0191] Coating solution 3
[0192] • 4-[(1E,3S)-3-vinyl-3,7-dimethylocta-1,6-dienyl]phenol (Bakuchiol): 5% by weight
[0193] • Polyglyceryl-10 laurate: 5% by weight
[0194] • CMC (carboxymethyl cellulose): 4% by weight
[0195] • Water: 86% by weight.
[0196] Coating process:
[0197] The coating is applied by means of a slot die process. A schematic diagram of the process is depicted in Figure 1 The sequence of process steps is as follows:
[0198] • The dimensions are 46 cm × 33 cm × 0.15 cm and the density is 0.022 g / cm 3 The porous collagen matrix substrate is placed on a movable stage
[0199] • The slot die is positioned at a distance of 700 µm from the plane of the substrate
[0200] • Arrange the table so that it moves horizontally under the slot die at a speed of 1 m / min
[0201] • When the slot die reaches position over the substrate, arrange the pump to pump the coating solution at a rate of 5 ml / min
[0202] • After the coating is evenly distributed on the substrate, turn off the pump
[0203] • The applied coating was dried in an oven at 90°C for 2 minutes so that a thin coating film was formed on the substrate. SEM images of the uncoated collagen matrix and the collagen matrix coated with CMC (coating solution 1) are provided in Figure 2 and Figure 3 middle.
[0204] Example 2.
[0205] A series of comparative experiments were carried out to demonstrate the advantageous properties of the product prepared by the method according to the invention. The results are summarized in Table 1.
[0206] The porous collagen matrix was coated by a non-contact slot die process using a 1.1% HA coating aqueous solution with an applied viscosity of 11.8 Pa·s (measured by viscometer) at a thickness of 20 µm (Experiment 1) and 40 µm (Experiment 2) as described in Procedure 2a below:
[0207] Process 2a
[0208] • The dimensions are 460 cm × 330 cm × 1.5 cm and the density is 0.024 g / cm 3 The porous collagen matrix substrate is placed on a movable stage
[0209] • The slot die is positioned at a distance of 350 µm (for 20 µm) and 700 µm (for 40 µm) from the plane of the substrate
[0210] • Arrange the table so that it moves horizontally under the slot die at a speed of 1 m / min
[0211] • When the slot die reached a position above the substrate, the pump was arranged to pump a 1.1% aqueous HA coating solution at a flow rate of 6.3 ml / min to form a 20.1 µm layer (experiment 1) or a 1.1% aqueous HA coating solution at a flow rate of 12.6 ml / min to form a 40.1 µm layer (experiment 2)
[0212] • After the coating is evenly distributed on the substrate, turn off the pump
[0213] • The applied coating was dried in an oven at 50°C for 2 minutes to form a thin coating film on the substrate.
[0214] The SEM images of the obtained materials are described as Figures 4 to 7 (Experiment 1) and Figures 8 to 11 (Experiment 2).
[0215] As a comparison, a porous collagen matrix was coated by a contact process with a 1.1% HA coating aqueous solution applied at a thickness of 30 µm (Experiment 3) as described in Procedure 2b below:
[0216] Process 2b
[0217] A scraper hand coater was placed on the collagen with the scraper at a distance of 30 µm from the surface of the collagen sheet (rectangular shape with 30 µm removed by CNC milling). The coating was then placed behind the scraper and the scraper was pulled over the surface of the collagen sheet. The surface was then wiped to remove the excess at the end of the coating length (this portion was not included in any measurement or consideration). The samples were dried in a convection oven at 50°C for 2 minutes.
[0218] The SEM images of the obtained materials are described as Figures 12 to 15 .
[0219] The sinking time in water and the water absorption of the obtained materials were measured (the results are summarized in Table 1), as described in Procedure 2c below:
[0220] Process 2c :
[0221] • Weigh the wire basket and record the weight (m1)
[0222] • Weigh the collagen sample, record the weight and insert the sample into the wire basket
[0223] • Weigh the wire basket containing the sample and record the weight (m2)
[0224] • Fill a 1000 ml beaker with RO water, controlling the water temperature
[0225] • Place the beaker of water on the scale and tare
[0226] • Drop the wire basket containing the sample horizontally from about 1 cm above the water surface into the beaker
[0227] • At the same time, start recording the time it takes for the wire basket containing the sample to completely sink below the water surface
[0228] • Remove the wire basket containing the sample from the water and hold it above the water for approximately 30 seconds to allow the sample to drain
[0229] • Weigh the wire basket containing the sample and record the weight (m3)
[0230] The water absorption rate is calculated as A=(m3-m2) / (m2-m1).
[0231] As a reference, the uncoated collagen matrix (Experiment 4, SEM image as shown in Figure 2 , Fig.16 and Fig.17The same measurements were performed on 2% finely ground collagen (dispersed 2% finely ground collagen in water by vigorous mixing, pouring the slurry onto tea paper, pumping the slurry through the tea paper to remove most of the water, and drying the remaining slurry in a convection oven until the residual moisture reached 5% to 12%) (Experiment 5) and printing paper (Example 6).
[0232] Table 1. Results of the measurements of sinking time and water absorption
[0233]
[0234] The purpose of experiment 5 is to simulate the compressed collagen foam film in US 3800792 A. As can be seen from Table 1, even when uncoated, both the printing paper and the ground and compressed collagen film have very poor water permeability and water absorption. If a coating is applied to the material, it is obvious that the value can be expected to drop further. On the contrary, the coated porous collagen (experiments 1 and 2) prepared by the slot die method according to the present invention and the comparative experiment (experiment 3) using the contact method have water absorption comparable to the uncoated porous collagen. However, compared with the material produced using the contact method, the material prepared by the non-contact slot die method according to the present invention has a further advantage of a shorter sinking time in water. For example, water takes about 40 seconds to pass through the material obtained in experiment 2, while the material obtained in experiment 3 takes about 60 seconds, although a thicker coating is applied in the first case. This can be explained as, when a contact method is adopted, the coating solution entering the inside of the hole can partially block the hole. When the coating passes through a porous substrate, it takes longer to dissolve it, which causes the sinking time to increase. Therefore, porous collagen coated by the slot die non-contact method wets out faster, which is advantageous especially in skin treatment.
[0235] This effect can also be seen from the SEM images. Top view of the coated collagen material obtained by the non-contact slot die method ( Figure 4 and Figure 8 ) clearly shows the holes and cavities, while the holes are barely visible when the contact method is used ( Fig.12 ). Differences can also be observed when comparing the bottom side of each material. Although the bottom view of the material prepared by the non-contact slot die method is similar to that of the uncoated porous collagen ( Figure 7 , Fig.11 and Figure 2 ) do not show significant differences compared to the 3D images, but the bottom side of the material obtained by the contact method clearly shows a reduction in porosity.
[0236] Example 3
[0237] Comparative experiments with a slot die coating solution having a viscosity of 3 Pa·s were performed as described in the following procedure:
[0238] The porous collagen matrix was coated with a thickness of 40 µm by applying a 0.4% HA coating aqueous solution with a viscosity of 3 Pa·s (measured by a viscometer) using a non-contact slot die process.
[0239] • The dimensions are 460 cm × 330 cm × 1.5 cm and the density is 0.024 g / cm 3 The porous collagen matrix substrate is placed on a movable stage
[0240] • The slot die is positioned at a distance of 600 µm from the plane of the substrate
[0241] • Arrange the table so that it moves horizontally under the slot die at a speed of 1 m / min
[0242] • When the slot die reaches a position above the substrate, a pump is arranged to pump a 0.4% HA coating aqueous solution at a flow rate of 12 ml / min to form a 40 µm layer
[0243] • After the coating is evenly distributed on the substrate, turn off the pump
[0244] • The applied coating was dried in an oven at 50°C for 3 minutes
[0245] The SEM images of the obtained materials are shown in Figures 18 to 22 As shown. It can be seen that the porous collagen cannot be effectively coated using a coating solution with a viscosity of 3 Pa·s. Top view of the coated sample ( Fig.18 ) and top view of uncoated material ( Figure 2 ) looks similar, indicating that the coating solution has passed through the holes to the bottom side, which can also be seen from Fig. 22 This results in a significant reduction in the thickness of the porous substrate, as shown in Fig.19 The cross-sectional view ( Fig. 20 and Fig.21 ) also showed that the porous structure was strongly affected, as almost no cavities and gaps were observed, only channels. HA from the coating solution can be seen on both sides of the porous substrate. Therefore, the viscosity of the initial coating solution is a key parameter for establishing a stable coating film on porous materials.
Claims
1. A method for preparing a composition comprising a porous material, wherein the porous material is substantially flat and comprises a plurality of open and interconnected pores having a pore surface, the method comprising the following steps: a) providing a porous material, wherein the porous material is substantially flat and comprises a plurality of open and interconnected pores having a pore surface, wherein the density of the porous material is between 0.01 g / cm 3 Up to 1 g / cm 3 In the range of 0.02 g / cm 3 Up to 0.05 g / cm 3 The most preferred range is 0.02 g / cm 3 Up to 0.04 g / cm 3 and wherein the average diameter of the pores is in the range of 10 µm to 150 µm; b) providing a coating solution, wherein the viscosity of the coating solution is in the range of 5 Pa·s to 20 Pa·s, preferably 8 Pa·s to 15 Pa·s, more preferably 10 Pa·s to 14 Pa·s; c) providing an applicator device for applying the coating solution onto the surface of the porous material, wherein the applicator device comprises a slot die; d) applying a quantitative amount of the coating solution onto the surface of the porous material by moving the porous material and the applicator device relative to each other at a speed of 0.1 m to 10 m per minute to coat the porous material and form a liquid layer; e) drying the liquid layer.
2. The method for preparing a composition comprising a porous material according to claim 1, wherein the density of the porous material increases by 10% to 30%, preferably by 10% to 20%, after the coating.
3. The method for preparing a composition comprising a porous material according to claim 1 or 2, wherein the coating solution applied to the surface of the porous material in step d) has a weight of 0.5 g / m 2 Up to 200 g / m 2 In the range of 10 g / m 2 Up to 100 g / m 2 In the range of 10 g / m 2 Up to 30 g / m 2 within the range. 4 . The method for producing a composition comprising a porous material according to claim 1 , wherein the coating solution comprises a solvent component and a film-forming component. 5 . The method for preparing a composition comprising a porous material according to claim 4 , wherein the solvent component is water.
6. The method for preparing a composition comprising a porous material according to claim 5, wherein the content of water in the coating solution is in the range of 0.5 wt % to 50 wt %, preferably in the range of 2 wt % to 35 wt %, more preferably in the range of 3 wt % to 30 wt %.
7. A method for preparing a composition comprising a porous material according to any one of claims 4 to 6, wherein the film-forming component is selected from hyaluronic acid (HA), polyacrylates, polyurethanes, and polysaccharides such as alginate, nanocellulose or carboxymethylcellulose (CMC), or a mixture thereof.
8. The method for preparing a composition comprising a porous material according to any one of claims 1 to 7, wherein the biomaterial is collagen.
9. Composition comprising a porous material obtainable by a process according to any one of claims 1 to 8.
10. A composition comprising: A porous substrate comprising a first major surface and a second major surface, wherein the porous substrate is substantially planar and comprises a plurality of open and interconnected pores having a pore surface, the pores extending through the porous substrate from the first major surface to the second major surface, wherein the average diameter of the pores is in the range of 10 μm to 150 μm; a coating on the first major surface and / or on the second major surface of the porous substrate, wherein the coating comprises hyaluronic acid (HA), polyacrylate, polyurethane, or a polysaccharide such as alginate, nanocellulose or carboxymethylcellulose (CMC), or a mixture thereof; The composition is characterized in that the water absorption rate is 10 g to 50 g per gram of the composition, preferably 20 g to 40 g per gram of the composition.
11. The composition of claim 10, wherein the coating of the coated porous material is bonded to the first major surface and / or the second major surface of the porous substrate by non-covalent bonds.
12. The composition of claim 10 or 11, wherein the coating on the first major surface and / or the second major surface of the porous substrate further comprises water.
13. The composition according to any one of claims 10 to 12, wherein the amount of the coating in the composition is in the range of 0.1% to 10% by weight, preferably 0.5% to 3% by weight, relative to the weight of the composition.
14. A composition according to any one of claims 10 to 13 for use as a medicament.
15. A composition according to any one of claims 10 to 13 for use in the treatment of stasis wounds, split skin grafts and ulcers.
Citation Information
Patent Citations
Insecticide
US2330234A
Laminated collagen film dressing
US3800792A
Coating edge control
US7097673B2